Profiles of Cancer Patients at Surgical Oncology Outpatient Clinic at Dharmais Cancer Hospital as National Referral Hospital in Indonesia from 2017 to 2021 - Sofyan, Rian Fabian; Ramadhan, Ramadhan; Purwanto, Denni Joko; Gautama, Walta; Dien, Alban W; Brahma, Bayu; Iskandar, Bob Andinata; Kurniawan, Febriyanto; Husein, Abdul Muhaimin; Sabatini, Nafilla Nesantya; Ginawang, Asto (Indonesian Journal of Cancer, 2024)
Background: Cancer is one of the leading causes of death in the world. Dharmais Cancer Hospital is set to be the National Cancer Center with an obligation to support all hospitals throughout the country that specialize in cancer. Surgical Oncology is one of the departments that handles the most cases in Dharmais Cancer Hospital. The types of cancers that are managed in Surgical Oncology Departments are breast cancer, head and neck cancer, thyroid cancer, skin cancer, and soft tissue cancer. Objective: This paper aims to find the newly diagnosed cancer patients’ characteristics and socioeconomic features in Dharmais National Cancer Center from 2017 to 2021. Methods: The study was a cross-sectional descriptive study using the medical record database of outpatients at Dharmais Cancer Hospital as a data collection method from 2017 until 2021. The sample size includes all new cancer patients in Dharmais Cancer Hospital that have been recorded. Result: Over 500,000 patients visited Dharmais Cancer Hospital in the last 5 years with an average of over 100,000 visits per year. Over 90% of the patients have solid tumors, and over eight thousand patients were admitted to the Surgical Oncology Outpatient Clinic, it was concluded that the most frequently diagnosed type of cancer is breast cancer (66.7%) of all types of cancer in the past 5 years. Most of the new patients are female (88.1%) with the most common age group of 40 to 55 years old (50.7%). Most of the patients are senior high school graduates (42.8%). Conclusions: The general characteristic of cancer patients is dominated by breast cancer patients, most patients are female, in the age group between 40 to 55 years old, and senior high school graduates. Further studies need to be done on each type of cancer to have a better understanding of the profiles and characteristics of solid cancer patients in Dharmais Cancer Hospital.